2008
DOI: 10.1007/s10495-008-0249-y
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-dioxin regulates Bovine Herpesvirus type 1 induced apoptosis by modulating Bcl-2 family members

Abstract: Exposure to environmental contaminants, like 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), leads to an increased susceptibility to infectious agents. Infection of bovine cells (MDBK) with Bovine Herpesvirus 1 (BHV-1) anticipates virus-induced apoptosis, suggesting an involvement of TCDD in virus infection. Herein we analyzed the effects of TCDD on apoptotic pathway in MDBK cells infected with BHV-1. After 12 h of infection, TCDD induced a significant increase in apoptotic cells. TCDD caused a dose-dependent up-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 36 publications
10
36
0
Order By: Relevance
“…In agreement with our previous reports [9], [50], [51], in the present study we first confirmed that TCDD induce a significant time and dose dependent viability decrease of BHV-1 infected cells. This effect is likely linked to a cell increased susceptibility to viral infection induced by the dioxin exposure, as described later.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In agreement with our previous reports [9], [50], [51], in the present study we first confirmed that TCDD induce a significant time and dose dependent viability decrease of BHV-1 infected cells. This effect is likely linked to a cell increased susceptibility to viral infection induced by the dioxin exposure, as described later.…”
Section: Discussionsupporting
confidence: 94%
“…Considering the concomitant widespread environmental diffusion of both dioxin and BHV-1, within a broader research project aimed to investigate the biological effects of dioxin in mammalian cells, herein we have explored the combined effects of TCDD exposure and BHV-1 infection on cellular iron metabolism. In particular, we focused on the possible impact of TCDD-dependent iron metabolism dysregulation on the progression of virus infection in MDBK cells, a useful and standardized epithelial-like in vitro model to study both virus replication and TCDD exposure in mammalian cells [9], [38], [45], [49]–[51]. As well to get an insight into the regulation of cellular iron homeostasis in presence of environmental toxins, these studies may have important repercussions especially in those geographic areas where dioxin and BHV-1 are concomitantly widespread.…”
Section: Discussionmentioning
confidence: 99%
“…Forced expression of the Bcl‐2 gene attenuated TCDD‐caused apoptosis of HUVECs, along with suppression of caspase 3 activity. In agreement with our observations, TCDD also promotes apoptosis of human trophoblast‐like JAR cells 53 and bovine MDBK cells 54 by down‐regulating expression of the Bcl‐2 gene. Given that EP3 inhibition or knockdown restored TCDD‐caused‐p38 MAPK activation and suppressed Bcl‐2 expression, EP3‐mediated activation of the p38MAPK/Bcl‐2 pathway contributes to apoptosis increased by TCDD in HUVECs.…”
Section: Discussionsupporting
confidence: 92%
“…Our data agree with results of Gautier et al [] who described induction of apoptosis in neuronlike cells infected with HSV‐1 at early stage of infections, with the results of Xu et al [] which reported similar findings for BHV‐1 infection in MDBK cell line and with several studies that reported concomitant caspase‐8 and caspase‐9 activation in various apoptotic systems [Aubert et al, ; St‐Louis and Archambault, ; Fiorito et al, ; Longo et al, ].…”
Section: Discussionsupporting
confidence: 93%